Insight into Nephrotoxicity and Processing Mechanism of Arisaema erubescens (Wall.) Schott by Metabolomics and Network Analysis - Wang M; Yang N; Wu X; Zou T; Zheng J; Zhu H; Zhao C; Wang J (Dove Medical Press, 2023)
Min Wang,1,2,* Na Yang,1,2,* Xu Wu,3 Ting Zou,3 Jiahui Zheng,3 Huaijun Zhu,1 Chongbo Zhao,3 Jing Wang3 1Department of Pharmacy, Nanjing Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, People's Republic of China; 2China Pharmaceutical University Nanjing Drum Tower Hospital, Nanjing, People's Republic of China; 3College of Pharmacy, Shaanxi University of Chinese Medicine, Xianyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Chongbo Zhao; Jing Wang, College of Pharmacy, Shaanxi University of Chinese Medicine, Xianyang, People's Republic of China, Email 2051077@sntcm.edu.cn; wangjing19890126@126.comBackground: Arisaematis Rhizome (AR) has been used as a damp-drying, phlegm-resolving, wind-expelling, pain-alleviating, and swelling-relieving drug for thousands of years. However, the toxicity limits its clinical applications. Therefore, AR is usually processed (Paozhi in Chinese) prior to clinical use. In this study, the integration of ultra-high performance liquid chromatography-quadrupole/ time-of-flight mass spectrometry-based metabolomics and network analysis was adopted to investigate the metabolic shifts induced by AR and explore the processing mechanism.Materials and Methods: Extracts of crude and processed AR products (1g/kg) were intragastrically administered to rats once daily for four consecutive weeks. The renal function was evaluated by blood urea nitrogen, creatinine, interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α), malondialdehyde (MDA), super oxide dismutase (SOD), the ratio of glutathione/glutathione disulfide (GSH/GSSH), glutathione peroxidase (GSH-Px) and histopathological examination. Furthermore, the chemical composition of AR was clarified by ultra-high performance liquid chromatography-quadrupole/ time-of-flight mass spectrometry, after which the integration of metabolomics and network analysis was adopted to investigate the metabolic shifts induced by AR and explore the processing mechanism.Results: Crude AR caused renal damage by stimulating inflammation and oxidative stress, as confirmed by the increased production of IL-1β, TNF-α and MDA, and decreased levels of SOD, GSH/GSSH and GSH-Px. Processing with ginger juice, alumen and bile juice alleviated the damage to kidney. Metabolomics results showed that a total of 35 potential biomarkers enriched in amino acid metabolism, glycerophospholipid metabolism, fatty acid-related pathways, etc. were deduced to be responsible for the nephrotoxicity of AR and the toxicity-reducing effect of processing.Conclusion: This work provided theoretical and data support for the in-depth study of the processing mechanism, showing that processing reduces AR nephrotoxicity through multiple metabolic pathways.Graphical Abstract: Keywords: Arisaematis rhizome, nephrotoxicity, processing, UPLC-Q/TOF-MS, metabolomics